Mengidentifikasi Efektivitas Sistem Saluran Drainase di Distrik Abepura, Jayapura, Papua: Studi Kasus: Kelurahan Wahno Distrik Abepura - Daniel B. Asmuruf; Monita .Y. Beatrik; Marsal Arung Lamba (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Wahno Subdistrict in Abepura District, Jayapura City, faces drainage problems that disrupt the area’s water management function. The varied topography, population growth, and the community’s habit of disposing waste into drainage channels have reduced the system’s capacity and caused frequent waterlogging during rainfall. This study aims to analyze the existing condition of the drainage channels in Wahno and to evaluate their effectiveness in conveying stormwater flow. The research methods include field surveys, channel dimension measurements, capacity calculations, and analysis of the effective volume compared to actual conditions affected by waste and sedimentation. The data were analyzed using quantitative and descriptive approaches to assess the performance level of the drainage system. The results show that most drainage channels in Wahno are not functioning optimally, with an average effectiveness of only 45–60% due to blockages caused by waste and sedimentation. The main factors reducing drainage effectiveness are decreased storage capacity, substandard design, and lack of regular maintenance. It is concluded that improvements to channel capacity, better waste management, and routine maintenance programs are necessary to enhance the drainage system’s effectiveness.